Estudio de efectos geofísicos del Terremoto de Limón mediante percepción remota y análisis hidrometereológico - Amador, Jorge A. (2011)
This work is related to the study of several aspects of some of the geophysical effects of the 22 April 1991 earthquake in the Atlantic Coast of Costa Rica. Changes in the shore line nearby Limón, associated to the uplift of the earth‘s crust, and sediment plumes and coastal currents are analyzed by means of LANDSAT (2 Abril 1991) and SPOT (19 June 1991) imagery. This analysis is complemented with hydrometeorological data and field work. In relation to the uplift of the earth's crust, the SPOT image shows an area of variable width to the north of Limón and in the neighborhood of the Pájaros and Uvita islands, that is not identified in the LANDSAT image prior to the event. Field work confirmed, that such an area is a mixture of dead coral reefs and consolidated sand. This uplift is of noncontinuous nature and is in the order of 40-50 cm near La Estrella river, 40 cm in the Muelle Alemán and approximately 2 m in Playa Bonita. Post-event precipitation rates and river flows were generally above normal means, such that together with the landslides, produced inusual sediment transport rates in the rivers of the region. These sediment discharges, specially in Banano and La Estrella rivers show well defined sediment concentration patterns that led to identify coastal currents with a principal component towards the north, in contrast to what has been published in the scientific literature.